Implementation and evaluation of real-time model predictive control for load fluctuations mitigation in all-electric ship propulsion systems. (15th November 2018) - Hou, Jun; Song, Ziyou; Park, Hyeongjun; Hofmann, Heath; Sun, Jing
Highlights: Real-time MPC has been implemented and evaluated in the physical testbed. Three special efforts are made to enable real-time implementation of MPC. Load fluctuations on the shipboard are addressed using real-time MPC. A filter-based algorithm is used to validate the effectiveness of MPC. The bus voltage variation and HESS loss can be reduced by up to 38% and 65%. Abstract: Electrification is a clear trend for both commercial and military ship development. Shipboard load fluctuations, such as propulsion-load fluctuations and pulse power loads, can significantly affect power system reliability. In order to address this issue, this paper explores a real-time model predictive control based energy management strategy for load fluctuation mitigation in all-electric ships. A battery combined with ultra-capacitor hybrid energy storage system (HESS) is used as a buffer to compensate load fluctuations from the shipboard network. In order to implement the proposed real-time MPC-based energy management strategy on a physical testbed, three special efforts have been made to enable real-time implementation: a specially tailored problem formulation, an efficient optimization algorithm and a multi-core hardware implementation. Given the multi-frequency characteristics of load fluctuations, a filter-based power split strategy is developed as a baseline control to evaluate the proposed MPC. Compared to the filter-based strategy, the experimental results show that the proposed real-time MPC achieves superior performance in terms of enhanced system reliability, improved HESS efficiency, long self-sustained time, and extended battery life. The bus voltage variation and hybrid energy storage losses can be reduced by up to 38% and 65%, respectively.